A new species of Anoplodactylus (Pycnogonida: Phoxichilidiidae) from Brazil, with a case of gynandromorphism in Anoplodactylus eroticus Stock, 1968 - Lucena, Rudá Amorim; Araújo, Joafrâncio Pereira De; Christoffersen, Martin Lindsey (Zootaxa, 2015)
A new species of Anoplodactylus was discovered in coral reefs from the State of Paraíba, northeastern Brazil. A. mirim sp. nov. is very small and is characterized for having 3 teeth on the cheliphores and a very small cement gland. It belongs to the A. pygmaeus complex, which contains very small species. A. batangensis is recorded for the first time along the Brazilian coast, and A. eroticus is recorded for the first time in the South Atlantic. We record the fifth known case of gynandromorphism, the fourth for Anoplodactylus, based on two specimens of A. eroticus.